Anxiolytic Effects of Diazepam: Relation with Serum Electrolytes, Plasma Osmolality and Systolic Blood Pressure in Rats (Journal of Fatima Jinnah Medical University, 2018)
Diazepam is an anxiolytic and anticonvulsant drug that also induces hypnosis. Changes in serum electrolyte balance, plasma osmolality and systolic blood pressure (SBP) are often associated with stressinduced anxiety. Administration of diazepam has been shown to decrease stress-induced enhancement of hypothalamic pituitary adrenal cortical (HPA) axis. The present is designed to monitor the anxiolytic effects of different doses of diazepam (1mg/kg, 2.5mg/kg and 5mg/kg) and its association with changes of serum electrolyte balance, plasma osmolality and SBP in rats. Administration of diazepam at doses of 1mg/kg, 2.5mg/kg and 5mg/kg elicited anxiolytic effects monitored in light-dark transition test and increased serum concentration of electrolytes and plasma osmolality. Serum levels of magnesium as well as SBP decreased. The results are discussed in context of anxiolytic effects of diazepam to be mediated via a modulation of stress- induced increase in the activity of HPA-axis and electrolytes balance.
Keywords: Diazepam, serum electrolyte, anxiolytic effects, osmolality